CARBONATE RESERVOIR CHARACTERIZATION OF BATURAJA FORMATION, PDW FIELD, PALEMBANG SUB-BASIN, SOUTH SUMATRA BASIN - Adiarsa, Rady
PDW field located in Palembang sub-Basin, South Sumatra Basin, has been proven to produce hydrocarbon, especially gas and condensate from Baturaja Formastion. Further field development needs to be done because of the evidence of five exploration well and it's production only derived from POP (Production On Perforation). By doing detailed analysis offacies deposition, diagenetic process, and rock typing, this analysis is expected to provide better result of carbonate reservoir characterization and potential so the development in PDW filed could be more efficient.